Interpretacja (z brulionem w tle). O czytaniu wiersza Dwaj prorocy. Próba głosu - Antoniuk, Mateusz (Przestrzenie Teorii, 2016)
The article regards the late Zbigniew Herbert’s poem entitled Dwaj prorocy. Próba głosu (The Two Prophets. The Attempt of the Voice). The author tries to prove that this poem resists interpretations seeking to create a clear and coherent analysis of its meaning. The article also focuses on a theoretical question: Can the draft of a poem prove useful in interpreting the finished and published literary work? The article was produced as part of the grant program entitled “The Zbigniew Herbert Archive – studies on documenting the creative writing process”.